2021
DOI: 10.3390/antibiotics10020108
|View full text |Cite
|
Sign up to set email alerts
|

Rhodomyrtone as a New Natural Antibiotic Isolated from Rhodomyrtus tomentosa Leaf Extract: A Clinical Application in the Management of Acne Vulgaris

Abstract: Rhodomyrtone, a plant-derived principal compound isolated from Rhodomyrtus tomentosa (Myrtaceae) leaf extract, was assessed as a potential natural alternative for the treatment of acne vulgaris. The clinical efficacy of a 1% liposomal encapsulated rhodomyrtone serum was compared with a marketed 1% clindamycin gel. In a randomized and double-blind controlled clinical trial, 60 volunteers with mild to moderate acne severity were assigned to two groups: rhodomyrtone serum and clindamycin gel. The volunteers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Users of antidepressive agents currently experience several adverse effects, such as weight gain, sexual dysfunction, and treatment resistance [ 4 , 44 , 45 ]. Studies have shown that Rho had the advantages of low drug resistance and toxicity [ 46 , 47 ], so Rho may be a promising antidepressant.…”
Section: Discussionmentioning
confidence: 99%
“…Users of antidepressive agents currently experience several adverse effects, such as weight gain, sexual dysfunction, and treatment resistance [ 4 , 44 , 45 ]. Studies have shown that Rho had the advantages of low drug resistance and toxicity [ 46 , 47 ], so Rho may be a promising antidepressant.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, the researcher developed a concise synthesis of the rhodomyrtone and isomeric acylphloroglucinols rhodomyrtosone B which displayed antibacterial activity [40]. Further research on rhodomyrtone proved the antibacterial properties and clinical management in Acne Vulgaris [41]. Recently, it was discovered that rhodomyrtone did not exhibit any toxicity in invertebrate or vertebrate models [42].…”
Section: Phytochemicals Screening Of Sertmentioning
confidence: 99%
“…The group of Voravuthikunchai et al obtained promising results in a study against psoriasis [17] and rhodomyrtone showed comparable effects to a drug against acne vulgaris in a double-blind controlled clinical trial. [18] Despite a lot of research, the exact mode of action of rhodomyrtone was not known until recently. Work by Götz et al showed that rhodomyrtone is a membrane-active compound that can lead to a breakdown of the membrane potential and release of ATP and cytoplasmic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Voravuthikunchai et al . obtained promising results in a study against psoriasis [17] and rhodomyrtone showed comparable effects to a drug against acne vulgaris in a double‐blind controlled clinical trial [18] . Despite a lot of research, the exact mode of action of rhodomyrtone was not known until recently.…”
Section: Introductionmentioning
confidence: 99%